Relationship of self-reported pica and avoidant restrictive food intake disorder symptomology with dimensions of impulsivity, perceived stress among Pakistani University students - Sara Aleem Haqqi; Siddrah Irfan (Journal of Eating Disorders, 2024)
Abstract Introduction Pica and avoidant/restrictive food intake disorder are two of the three new eating and feeding disorders introduced in the DSM-5, this inclusion has drawn attention to the immediate need for research into their prevalence, diagnostic assessment, underlying risk factors and optimal treatment. There are very few studies available that explored the predictors or causes of these eating disorders specifically in Pakistani context. Objectives The objectives of the current study include (a) to estimate the presence of pica and avoidant/restrictive food intake disorder symptomology among young adults in Pakistan, (b) to examine the relationship between dimensions of impulsivity, stress and presence of pica and avoidant/restrictive food intake disorder, (c) to explore the mediation role of stress. Methods The sample consisted of 660 young adults with age range 18–25 years, recruited through convenient sampling. The respondents were provided with a questionnaire comprising of an informed consent, a demographic information sheet and self-report measures including PARDI-AR-Q to assess symptomology of pica and avoidant/restrictive food intake disorder, UPPS-P Impulsive Behaviour Scale to assess dimensions of impulsivity and Perceived Stress Scale to measure perceived stress. Results The findings show that 28 participants (4.2%) reported Pica symptomology, of which eleven participants indicated that they currently consume more than one non-food item. 19 respondents (2.8%) reported avoidant/restrictive food intake disorder symptomology. 13 respondents reported varying degrees of all three symptom clusters namely sensory based food avoidance, lack of interest in food, and fear of negative consequences of eating. Additionally, each of the dimensions of impulsivity was found to be positively correlated to the presence of pica and avoidant/restrictive food intake disorder. Perceived stress was identified as a mediating factor between each of the dimensions of impulsivity and presence of pica and avoidant/restrictive food intake disorder. Conclusion Although current study focused on a particular age range, it has drawn attention to the necessity of screening and investigating other strata of Pakistani population for pica and avoidant/restrictive food intake disorder. The clinical utility of the present research resided in the identification of factors associated with pica and avoidant/restrictive food intake disorder, an information which can be used to tailor psychological interventions, modify existing ones, and inform the future research on evidence-based treatment.